(untitled) (Baghdad Science Journal, 2008)
This study was carried out to investigate the cytogenetic effects of crude aqueous extract of Lycium barbarum on the roots tip of Allium cepa Using three concentration 125, 25, 50 mg/ ml for 2, 4, 6 hours treatment periods.This study were included some cytogenetic analysis such as mitotic index , phase index and chromosome aberration. The data showed that the treatment with 50mg/ml for 6huors led to reduce the mitotic index less than 50% . This reduction considered to have toxic and sublethal effect . These results revealed mutagenic potency by inducing differents type of chromosome aberration.